Comparative micromorphology and phylogenetic analysis of three Salvia species (Lamiaceae) endemic to Türkiye - Kahraman, Ahmet; Tutus, Ramazan; Memon, Abdulrezzak (Phytotaxa, 2025)
Micromorphology of trichomes and leaf epidermal cells of three morphologically similar species endemic to Türkiye, Salvia hedgeana, S. huberi and S. rosifolia, are investigated using light microscopy (LM) and scanning electron microscopy (SEM). The main objectives of the present study are to survey these characters for the first time and to assess their significance for distinguishing among these species. In addition to micromorphological analyses, phylogenetic relationships of the studied Salvia species with other Salvia taxa are inferred using the rpl32 gene region and the rpl32–trnL intergenic spacer. Three basic types of trichomes can be identified: peltate glandular, capitate glandular and eglandular trichomes. The capitate glandular trichomes may be subdivided into four subtypes according to shape of head cells and number of stalk cells. The eglandular trichomes are in turn subdivided into two subtypes: acicular and flagelliform (whip-like). Based on cell number, acicular eglandular trichomes are further divided in four shapes: unicellular, bicellular, three-celled and more than three celled. The peltate trichomes are present on the investigated aerial parts of the species. However, the capitate and eglandular trichomes types vary in distribution, density and size among the species. Some differences have been also observed in the morphology of epidermal cells and the number of stomata on the blades. The phylogenetic analysis reveal clear distinctions among the Salvia species, aligning with the micromorphological clustering observed in the Principal Component Analysis (PCA).